Ecotourism in the IMT-GT region issues and challenges - Kayat, Kalsom (Universiti Utara Malaysia, 2006)
As a new concept, ecotourism is surrounded by countless issues and inquiries.The dimensions of issues include the management and policies for ecotourism development, the impacts from ecotourism operation and ecotourism marketing. Several of these issues were addressed by the paper presenters at the IMT-GT International Conference on Ecotourism that was held in December 2003 at Universiti Utara Malaysia (UUM).This book consists of a chosen number of papers presented at the conference that may become a good resource for future discussions and research in the area of ecotourism in the IMT-GT region as well as in the global context.